2009
DOI: 10.1080/01140670909510273
|View full text |Cite
|
Sign up to set email alerts
|

Response of cowpea (Vigna unguiculata) to salinity and irrigation regimes

Abstract: The effects of salinity and irrigation regimes on yield, growth, and water consumption of cowpea (Vigna unguiculata) were determined in two different experiments. The first experiment focused on cowpea responses to irrigation water with six different levels of salinity (0.7, 2.0, 3.0, 4.0, 5.0, and 7.0 dS m-1). In the second experiment four different amounts of water (1.43, 1.0, 0.75, and 0.50 times of depleted water) were applied to cowpea plants. Seed and pod yields of cowpea decreased significantly for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 10 publications
10
40
0
Order By: Relevance
“…According to Duzdemir et al (2009), the pea is a crop which is very sensitive to water stress. Giordano (1997) also highlights that excess of water can affect plant development, due to lodging, an increase of fungal diseases and uneven maturity.…”
Section: Palavras-chavementioning
confidence: 99%
“…According to Duzdemir et al (2009), the pea is a crop which is very sensitive to water stress. Giordano (1997) also highlights that excess of water can affect plant development, due to lodging, an increase of fungal diseases and uneven maturity.…”
Section: Palavras-chavementioning
confidence: 99%
“…Water stress possibly reduced pollen fertility, increased pod abortion and reduced pod filling in soybean that resulted in decreased number of filled pods (Khan et al, 2016;Duzdemir et al, 2009). The maximum 100-seed weight of 10.62 g was obtained from control which was identical to water stress during 4 th to 6 th weeks after emergence (10.52 g) and 6…”
Section: Yield Attributes and Yieldmentioning
confidence: 99%
“…Plants are unable to maintain metabolic activities, especially the turgidity of cell for normal growth under salt or water stress conditions, and that finally resulted yield reduction (Khan et al, 2016). Salinity or water shortage decreased pod number in pea (Duzdemir et al, 2009) and soybean (Chowdhury et al, 2015). Soybean is classified as a moderately salt sensitive crop (Katerji et al, 2003) and denoted as sensitive to drought stress, especially at the early reproductive stage (Westgate and Peterson, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Prepared saline waters for each treatment were stored in 100 liter-plastic containers. EC i of these waters were controlled by an EC/pH meter (Jenway 430 model) before each irrigation application and the adjustment was done if necessary (Ünlükara et al 2008;Düzdemir et al 2009;Ünlükara et al 2010). Tap water (EC i = 0.65 dS m -1 ) was used to irrigate of the control treatment in the salinity experiment and the treatments of the irrigation regime experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Letey & Dinar (1986) stated that different conditions for evapotranspiration were obtained by applying different soil moisture regimes but rarely by using saline water. Ozturk et al (2004) reported decreasing effect of salinity on water consumption for lemon balm, Yurtseven et al (2005) for tomato, Ünlükara et al (2008) for okra, Düzdemir et al (2009) for cowpea, Ünlükara et al (2010) for eggplant, Kurunc et al (2011) for bell pepper. Plant water consumption also changes with changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%